Injury pattern in senior squash and tennis players - Goertzen, M. (1997)
A five-year prospective study was performed with 104 senior tennis players and 85 senior squash players, to investigate and compare injury patterns. Players were asked to complete questionnaires regarding previous injuries, tennis and squash experience and ability, medical illnesses and other demographic data. A complete musculoskeletal history and physical examination was performed annually. The proportion of squash injuries was found to be higher than in tennis. Acute traumatic injuries were seen mainly in squash players, most affecting the face and ankle. Senior squash players also showed a higher incidence of lower extremity injuries. Senior tennis players demonstrated no significant difference in the relationship of lower and upper extremity injury profile.